Hadith #2321 - Sunan Abi Dawud - Ahmed bin Manay' أحمد بن منيع; Amr bin al-Harith bin Abi Darar; ibn Mas'ud; Isa bin Dinar al-Khuza'i عيسى بن دينار الخزاعي أبو علي; Yahya bin Zakaria bin Abi Zaida يحيى بن زكريا بن أبي زائدة (Sunan Abi Dawud)
‘Umar b. ‘Abd al-‘Aziz wrote (a letter) to the people of Basrah: It has reached us from the Messenger of Allah (ﷺ), like the tradition narrated by Ibn ‘Umar from the Prophet (ﷺ). This version adds: The best calculation is that when we sight the moon of Sha’ban on such-and-such date, fasting will being on such-and-such dates, Allah willing, except they they sight the moon before that (date).
Grade: Da'if

Hadith #2881 - Sunan Abi Dawud - Ahmed bin Manay' أحمد بن منيع; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Ikrama عكرمة; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Zakaria bin Ishaq al-Makki زكريا بن إسحاق المكي (Sunan Abi Dawud)
A woman said: Messenger of Allah, my mother suddenly died; if it had not happened, she would have given sadaqah (charity) and donated (something). Will it suffice if I give sadaqah on her behalf? The Prophet (ﷺ) said: Yes, give sadaqah on her behalf.
Grade: Sahih

Hadith #3587 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abdullah ibn al-Zubayr; Ahmed bin Manay' أحمد بن منيع; Mus'ab bin Thabit bin 'Abdullah مصعب بن ثابت بن عبد الله بن الزبير (Sunan Abi Dawud)
Abu ‘Uthman al-Shami, whose name is Hariz bin ‘Uthman, told me. I think I did not see anyone from Syria better than him.
Grade: Sahih

Hadith #4145 - Sunan Abi Dawud - Ahmed bin Manay' أحمد بن منيع; Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Urwa ibn al-Zubayr عروة بن الزبير; Uthman bin Muhammad (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said to me: Have you made cushions ? I said: How can we afford cushions ? He said: Soon you will have cushions.
Grade: Sahih

Hadith #4429 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ahmed bin Manay' أحمد بن منيع; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Fdyl bin Husayn bin Talha فضيل بن حسين بن طلحة; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The narrator Hasan b. “All said: The transmitters have differed in the wordings (of this tradition) reported to me. Some said: He (Ma’iz) was tied to a tree, and others said: He was made to stand.
Grade: Hasan

Hadith #4792 - Sunan Abi Dawud - Ahmed bin Manay' أحمد بن منيع; Amr bin al-Hythm bin Qtn عمرو بن الهيثم بن قطن; Anas ibn Malik; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
A man asked permission to see the Prophet (ﷺ), and the Prophet (ﷺ) said: He is a bad member of the tribe. When he entered, the Messenger of Allah (ﷺ) treated in a frank and friendly way and spoke to him. When he departed , I said: Messenger of Allah! When he asked permission, you said: He is a bad member of the tribe, but when he entered, you treated him in a frank and friendly way. The Messenger of Allah replied: Aisha! Allah does not like the one who is unseemly and lewd in his language
Grade: Hasan Sahih

Hadith #5141 - Sunan Abi Dawud - Abdullah bin Dinar عبد الله بن دينار العدوي; Ahmed bin Manay' أحمد بن منيع; al-Laith bin Sa'd الليث بن سعد; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; ibn Umar (Sunan Abi Dawud)
A man’s reviling of his parents is one of the grave sins. He was asked : Messenger of Allah! How does a man revile his parents? He replied: He reviles the father of a man who then reviles his father, and he reviles a man’s mother and he reviles his.
Grade: Sahih

Hadith #5241 - Sunan Abi Dawud - Aabad bin 'Aabad bin Habib عباد بن عباد بن حبيب بن المهلب; Abu Dharr al-Ghaffari; Ahmed bin Manay' أحمد بن منيع; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Yahya bin Aqyl يحيى بن عقيل; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
I asked Hisham ibn Urwah about the cutting of a lote-tree when he was leaning against the house of Urwah. He said: Do you not see these doors and leaves? These were made of the lote-tree of Urwah which Urwah used to cut from his hand? He said: There is no harm in it. Humayd’s version adds: You have brought an innovation, O Iraqi! He said: The innovation is from you. I heard someone say at Mecca: The Messenger of Allah (ﷺ) cursed him who cuts a lote-tree. He then mentioned the rest of the tra
Grade: Hasan

Hadith #5249 - Sunan Abi Dawud - Abdur Rahman bin 'Abdullah bin Sabit عبد الرحمن بن عبد الله بن سابط; Ahmed bin Manay' أحمد بن منيع; al-'Abbas ibn 'Abd al-Muttalib; Marwan bin Mua'wiya al-Fazari مروان بن معاوية الفزاري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Kill all the snakes, and he who fears their revenge does not belong to me.
Grade: Sahih